2005
DOI: 10.1111/j.1600-0765.2005.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalisaffects host collagen degradation by affecting expression, activation, and inhibition of matrix metalloproteinases

Abstract: Porphyromonas gingivalis increased the collagen degrading ability of HGFs, in part, by increasing MMP activation and by lowering the TIMP-1 protein level, as well as by affecting the mRNA expression of multiple MMPs and TIMPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
93
3
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 33 publications
9
93
3
3
Order By: Relevance
“…Much attention has been given to proteinase produced by host cells. MMP, enzymes secreted by endothelial cells, macrophages, and fibroblasts, are known to be involved in tissue remodeling, organogenesis, angiogenesis, wound repair, and inflammatory cellular infiltration by degrading extracellular matrix [16,30] . At the inflammatory site, inflammatory cells are mobilized and MMP are produced as pro-enzymes and activated by various stimulatory factors [30] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Much attention has been given to proteinase produced by host cells. MMP, enzymes secreted by endothelial cells, macrophages, and fibroblasts, are known to be involved in tissue remodeling, organogenesis, angiogenesis, wound repair, and inflammatory cellular infiltration by degrading extracellular matrix [16,30] . At the inflammatory site, inflammatory cells are mobilized and MMP are produced as pro-enzymes and activated by various stimulatory factors [30] .…”
Section: Discussionmentioning
confidence: 99%
“…At the inflammatory site, inflammatory cells are mobilized and MMP are produced as pro-enzymes and activated by various stimulatory factors [30] . Recent studies demonstrated that MMP expression was upregulated by pro-inflammatory mediators including IL-1 and TNF-α [16] . Taken together, these findings suggest that although the prtC gene product may not be a true bacterial collagenase, it could have a strong effect on inducing host cells to secret inflammatory cytokines and further enhance the collagenase activity of host cells such as MMP, which lead to the destruction of periodontal connective tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell viability and sublethal cytotoxic effects on the cells were determined according to previous studies [11,12]. A control group comprised HGFs without treatment.…”
Section: Introductionmentioning
confidence: 99%